1997
DOI: 10.1103/physrevb.55.11191
|View full text |Cite
|
Sign up to set email alerts
|

Pressure dependence of Raman linewidths in ices VII and VIII

Abstract: Vibrational modes of D 2 O ices VII and VIII have been measured by Raman scattering in a diamond-anvil cell up to 25 GPa, between 80 and 300 K. The linewidths and frequency variation with pressure and temperature of T , a low-frequency O-O stretching phonon mode, and of 1 , the high-frequency totally symmetric O-H stretching vibron, are analyzed, and their behavior at the phase transition from ice VIII to ice VII is explained. The discontinuities in the linewidth and frequency of the phonon, which occur when g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
1
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 37 publications
1
12
1
1
Order By: Relevance
“…In particular, while no Raman activity is expected in clean samples below 360 cm −1 , a broad band systematically appears at low frequency in ceramics [17,19], twice-peaked around 250 and 320 cm −1 , with an intensity which differs from sample to sample of a same bulk composition [17]. We attribute this band to a high density of states of disorder-activated acoustic phonons, in analogy to what is found, e.g., in ice VII [20]. Having shown that the vibrational spectra of B 4 C can be consistently interpreted in terms of a carbon atom occupying one of the polar sites, we consider now its elastic properties, which have recently attracted some interest [10].…”
mentioning
confidence: 63%
“…In particular, while no Raman activity is expected in clean samples below 360 cm −1 , a broad band systematically appears at low frequency in ceramics [17,19], twice-peaked around 250 and 320 cm −1 , with an intensity which differs from sample to sample of a same bulk composition [17]. We attribute this band to a high density of states of disorder-activated acoustic phonons, in analogy to what is found, e.g., in ice VII [20]. Having shown that the vibrational spectra of B 4 C can be consistently interpreted in terms of a carbon atom occupying one of the polar sites, we consider now its elastic properties, which have recently attracted some interest [10].…”
mentioning
confidence: 63%
“…Besson et al (28) observed a roughly parabolic behavior of the υ 1 vibron line width in D 2 O ices VII and VIII with a clear minimum at ∼13 GPa, implying increased disorder above this pressure. Meanwhile, measurements of the VII-VIII transition temperature by Pruzan et al (29,30) show that this begins to decrease markedly between 10 and 18 GPa (being constant below this pressure).…”
Section: Resultsmentioning
confidence: 99%
“…A possible transition near 2-3 GPa in ice VIII ͑referred to as ice VIIIЈ͒ has been reported on the basis of neutron diffraction, 7 Raman, 8 and far-infrared ͑FIR͒ measurements. 9 Theoretical calculations suggest that the ice VIII transition could arise from differences in the way that the hydrogenbonded network relaxes relative to the non-hydrogen-bonded structure.…”
Section: Introductionmentioning
confidence: 99%